2018 26th European Signal Processing Conference (EUSIPCO) 2018
DOI: 10.23919/eusipco.2018.8553378
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Multiclass Inference for MI-BCIs Using Large Multiscale Temporal and Spectral Features

Abstract: Accurate, fast, and reliable multiclass classification of electroencephalography (EEG) signals is a challenging task towards the development of motor imagery brain-computer interface (MI-BCI) systems. We propose enhancements to different feature extractors, along with a support vector machine (SVM) classifier, to simultaneously improve classification accuracy and execution time during training and testing. We focus on the well-known common spatial pattern (CSP) and Riemannian covariance methods, and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 10 publications
0
64
0
Order By: Relevance
“…A visual illustration of a single trial is shown in Figure 6(a). Previous studies that used this dataset, have mostly considered the [3−6] s window as the interval during which motor imagery tasks are performed [37,42,23,25,52,69,72] for the analysis. Therefore, we also extracted this 3-s motor imagery interval from each trial.…”
Section: Methodsmentioning
confidence: 99%
“…A visual illustration of a single trial is shown in Figure 6(a). Previous studies that used this dataset, have mostly considered the [3−6] s window as the interval during which motor imagery tasks are performed [37,42,23,25,52,69,72] for the analysis. Therefore, we also extracted this 3-s motor imagery interval from each trial.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the improvement brought by Riemannian geometry is due to the consideration of the non-linear information contained in the covariance matrices, thus better extracting features, which are usually discarded by the linear space filtering methods. On the basis, the multi-band Riemannian method can use a small amount of calibration data to extract the noise robust features, and achieve better results ( Islam et al, 2017 , 2018 ; Hersche et al, 2018 ). In order to further improve the multi-band Riemannian method, this article uses a non-parametric method of MANOVA based on the sum of squared distances ( Anderson, 2001 ) to select frequency bands that are separable for specific subjects, and multi-scale division is performed on the multi-channel EEG signals in these frequency bands.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-band selection method adopted can be based on the mutual information between features and class labels, thereby effectively extract the frequency band of a specific subject, and further improve the performance of MI-BCI ( Islam et al, 2018 ). In addition, in order to overcome the limitation of using fixed band window analysis in MI-BCI, Hersche et al (2018) proposed a multi-scale filter bank TSM (MFBTSM), in which FB contains the frequency bands are multi-scale and overlapping. At the same time, multi-scale and overlapping time windows are divided, so that multiple time windows are used to analyze EEG trials and perform FB analysis in each time window.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that used this dataset, have mostly considered the [3 − 6] s window as the interval during which motor imagery tasks are performed [37, 42, 23, 25, 52, 69, 72] for the analysis. Therefore, we also extracted this 3-s motor imagery interval from each trial.…”
Section: Methodsmentioning
confidence: 99%